Incidence of immunodeficiency and leukemia viruses inFelis catusin the Veterinary Clinic Gattos Tunja-Boyacá: IMMUNODEFICIENCY - Lagos-López, Mayer Isnardo; Massey Malagón, Delia Yuliana; Cuervo-Saavedra, Sandra Rocio (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Feline leukemia (FeLV) and immunodeficiency (FIV) are very complex diseases and are not yet fully known. They are persistent infections, with alterations or imbalances in the immune system. The increase in feline population worldwide and in Colombia can be observed, as in the city of Tunja, therefore, infectious diseases such as those mentioned above, also prevail, and as a consequence, need to be diagnosed, however, in Colombia, there are few studies that allow to know the prevalence of Leukemia and Immunodeficiency or its diagnosis is underestimated, with the realization of this research is sought, to establish the incidence of the immunodeficiency and feline leukemia viruses in the population of cats in the city of Tunja, study, carried out with cats (chosen for convenience), independent of race or sex, non-symptomatic, with age range from seven months of age (estimated by the analysis of dental arch), which are received during a period of six months at the veterinary clinic Gattos. Because of the easy transmission of leukemia, it is important to prevent infection through the isolation of sick animals and the vaccination of healthy animals, in the case of immunodeficiency, to avoid fights between healthy and sick cats.